Jewish Latin American Artists : Perspectives from the Global South - Fattal, Laura, (Jewish Latin America ;, 2025)
Jewish visual artists living and working in Latin America during the 20th and 21st centuries broaden an appreciation of the art of the Americas. The anthology addresses an often underacknowledged Jewish presence as part of the aesthetic of the global south providing the general public and scholars with in-depth insights. The artists' dynamic prints, sculptures, paintings, and photographs explore aspects of modernist abstraction, and at times, indigenous materials, sardonic commentary on consumerism, and utopian ideals in their works of art. The anthology begins to fill a void of the contribution of Jewish Latin American artists born in Europe who immigrated to Latin America and others born there.